Zoltán Tildy and 1919 - CSŰRÖS, András (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
After the Second World War, Zoltán Tildy held the offices of Prime Minister of Hungary and later President of the Republic. As a figure of historical significance, his career is the subject of considerable controversy. The central question is why Zoltán Tildy did not take a more robust stance against the nascent communist dictatorship. A number of questions about his life’s journey can be answered by attempting to comprehend his thought process through an earlier historical moment. For the first time since Lenin, a proletarian dictatorship was proclaimed in Hungary. Under Béla Kun’s regime, many people enthusiastically embraced the Soviet Republic, only to be disappointed by it due to several misunderstandings. One of the figures associated with this enthusiasm and early survival technique was Tildy, who is associated with the communist leadership. He established a Reformed organization in Somogy County, called the Pastors’ Trade Union. Furthermore, his life was also marked by the death of his father-in-law from the same period, an episode that is therefore also covered in this paper.